1999
DOI: 10.1021/ef980161c
|View full text |Cite
|
Sign up to set email alerts
|

Observations of Heterogeneity in Large Pulverized Coal Particles

Abstract: The heterogeneity of the 125-212 µm size cuts from four pulverized coal samples from the United Kingdom, United States, and South Africa has been examined in detail by means of density separation and optical and scanning electron microscopy. While average properties of the overall size cut samples are similar to those of the parent coals, a high degree of heterogeneity exists between average compositions for the different density cuts within each sample, between different particles within the same density cuts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 5 publications
1
5
0
Order By: Relevance
“…Therefore, it is reasonable to conclude that ash has an impact on the physical structure of the residual char. This observation supports the conclusion of Gibbins et al . that both coal maceral and ash should be considered to provide reasonable explanation to pf coal combustion behavior.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Therefore, it is reasonable to conclude that ash has an impact on the physical structure of the residual char. This observation supports the conclusion of Gibbins et al . that both coal maceral and ash should be considered to provide reasonable explanation to pf coal combustion behavior.…”
Section: Resultssupporting
confidence: 91%
“…In investigating the heterogeneity of large pf coal particles during the devolatilization process, Gibbins and his colleagues found some synergic effects during devolatilization, and suggested that the ability of using relatively pure macerals (from hand-picking, or micronizing, demineralization, and density separation) to represent actual pf combustion behavior may be limited. In their study, a wide range of particle mineral content was also observed, and the minerals were generally well dispersed and frequently associated with the inertinite maceral.…”
Section: Introductionmentioning
confidence: 99%
“…Pulverized coal is a mixture of heterogeneous particles . The chemical and physical properties of coal, such as H/C ratio, ash content, internal surface area and sulfur content, may depend on the initial particle size, but particle-to-particle differences between particles of equal size exist.…”
Section: Resultsmentioning
confidence: 99%
“…These coal blocks were prepared by mounting in resin followed by drying. The blocks were polished using a Struers TegraForce-1 polishing machine, followed by maceral group analyses using a 500 point-count method [43]. The block-examining equipment was a Leica DM4500P petrography microscope [42], which has a 50Â lens and a 10Â internal.…”
Section: Petrographic Analysismentioning
confidence: 99%